Attosecond streaking metrology with isolated nanotargets. (5th January 2018) - Liu, Q; Seiffert, L; Trabattoni, A; Castrovilli, M C; Galli, M; Rupp, P; Frassetto, F; Poletto, L; Nisoli, M; Rühl, E; Krausz, F; Fennel, T; et al.
Abstract: The development of attosecond metrology has enabled time-resolved studies on atoms, molecules, and (nanostructured) solids. Despite a wealth of theoretical work, attosecond experiments on isolated nanotargets, such as nanoparticles, clusters, and droplets have been lacking. Only recently, attosecond streaking metrology could be extended to isolated silica nanospheres, enabling real-time measurements of the inelastic scattering time in dielectric materials. Here, we revisit these experiments and describe the single-shot analysis of velocity-map images, which permits to evaluate the recorded number of electrons. Modeling of the recorded electron histograms allows deriving the irradiated nanoparticle statistics. Theoretically, we analyze the influence of the nanoparticle size on the field-induced delay, which is one of the terms contributing to the measured streaking delay. The obtained new insight into attosecond streaking experiments on nanoparticles is expected to guide wider implementation of the approach on other types of nanoparticles, clusters, and droplets.